Hyperphosphatemic Tumoral Calcinosis after Total Knee Arthroplasty - Takeshi Mochizuki; Katsunori Ikari (Case Reports in Orthopedics)
We report a case of hyperphosphatemic tumoral calcinosis (TC) that occurred after total knee arthroplasty. A 64-year-old Japanese man presented with painful swellings in both shoulders, the left elbow, and the right hip that developed after he underwent total knee arthroplasty (TKA). The pathology of the patient’s bone at the time of TKA included a thick osteoid seam with calcareous deposition at the margin of the trabecular bone, which is not generally seen in osteoarthritis. Computed tomography scans of the swollen joints demonstrated leaflet and amorphous calcification masses around the joints. We diagnosed the patient with TC. The present case highlights that TC lesions are rare but should be considered in the differential diagnosis of subcutaneous soft and hard masses around the joint.